Tailored Sample Mounting for Light-Sheet Fluorescence Microscopy of Clarified Specimens by Polydimethylsiloxane Casting - Di Giovanna, Antonino Paolo; Credi, Caterina; Franceschini, Alessandra; Müllenbroich, Marie Caroline; Silvestri, Ludovico; Pavone, Francesco Saverio (Frontiers in Neuroanatomy, 2019)
The coupling of biological tissue clearing methods with light-sheet fluorescence microscopy (LSFM) allows acquiring images of specific biological structures of interest at whole organ scale and microscopic resolution. Differently to classical epifluorescence techniques, where the sample is cut into slices, LSFM preserves the whole organ architecture, which results particularly important for investigation of long-range neuronal circuits. This imaging modality comes with the need of new protocols for sample mounting. Gel matrix, hooks, tips, glues, and quartz cuvettes have been used to keep whole rodent organs in place during image acquisitions. The last one has the advantage of avoiding sample damage and optical aberrations when using a quartz refractive index (RI) matching solution. However, commercially available quartz cuvettes for such large samples are expensive. We propose the use of polydimethylsiloxane (PDMS) for creating tailor-made cuvettes for sample holding. For validation, we compared PDMS and quartz cuvettes by measuring light transmittance and performing whole mouse-brain imaging with LSFM. Moreover, imaging can be performed using a cheap RI matching solution, which further keeps down the cost of the imaging process. Worth of note, the RI matching solution used in combination with PDMS leads to a moderate expansion of the sample with respect to its original size, which may represent an advantage when investigating small components, such as neuronal processes. Overall, we found the use of custom-made PDMS cuvettes advantageous in term of cost, image quality, or preservation of sample integrity with respect to other whole-mouse brain mounting strategies adopted for LSFM.